Well-being impact on banking systems - Iulia Cristina Iuga; Larisa-Loredana Dragolea (Journal of Risk and Financial Management, 2021)
The present research focuses on the influence of the well-being indicators, more specifically, the indicators reflecting the life quality on the banking systems evolution from the EU member states. The study offers a unique approach to comparing the two country groups: the eurozone countries and the EU noneuro countries during the 2008-2019 period. The model is estimated with the help of the OLS method by using panel data. The study aims to identify which life quality indicators significantly influence the EU member states' banking systems evolution and develop models dividing the countries into two groups. Our conclusions show that, among all the determinant factors analysed in this study, household consumption and internet users strongly influence all EU countries' banking systems.
Keywords: 330; banking systems; eurozone countries; noneuro countries; quality of life indicators; regression analysis; well-being